Near-death experiences - Karst, Ken (Karst, Ken. Enduring mysteries., 2019)
Examines the phenomena of near-death experiences, citing their prevalence throughout history and their consistency in people across cultures and times, and explores research done on people who have had NDEs. Includes a glossary and color photographs.